The RNA-Seq data analysis shows how the ontogenesis defines aging - Salnikov, Lev; Goldberg, Saveli; Rijhwani, Heena; Shi, Yuran; Pinsky, Eugene (Frontiers in Aging, 2023)
This paper presents a global statistical analysis of the RNA-Seq results of the entire Mus musculus genome. We explain aging by a gradual redistribution of limited resources between two major tasks of the organism: its self-sustenance based on the function of the housekeeping gene group (HG) and functional differentiation provided by the integrative gene group (IntG). All known disorders associated with aging are the result of a deficiency in the repair processes provided by the cellular infrastructure. Understanding exactly how this deficiency arises is our primary goal. Analysis of RNA production data of 35,630 genes, from which 5,101 were identified as HG genes, showed that RNA production levels in the HG and IntG genes had statistically significant differences (P-value <0.0001) throughout the entire observation period. In the reproductive period of life, which has the lowest actual mortality risk for Mus musculus, there was a significant decrease in gene production by the time of its ending. A statistically significant change in the dynamics of age-related production occurred only in HG genes in contrast to IntG (p-value = 0.0045), showing the age-related dynamics of cellular resource consumption. The link between ontogenesis and aging is rather obvious. We proceed from the position that aging itself is a by-product of ontogenesis program implementation. The activity dynamics of gene blocks responsible for the regulation of ontogenesis show a rapid decrease in their activity, anticipating the same dynamics in the HG gene group. The main conclusion of this work is the fact of asymmetric effect of ontogenetic regulators on the cellular infrastructure represented by HG group in the genome, creating in cells a deficit in the function of their infrastructure.